2007
DOI: 10.1002/ppap.200730203
|View full text |Cite
|
Sign up to set email alerts
|

PECVD of Low Carbon Content Silicon Nitride-Like Thin Films with Dimethylaminosilanes

Abstract: Three dimethylaminosilanes, characterized by a different number of NMe2 groups bonded to silicon, have been compared as precursors in silicon nitride‐like films plasma enhanced chemical vapour deposition (PECVD). The effect of input power on the chemical characteristics of the coatings has been studied by means of FT‐IR and XPS analyses, while the plasma phase composition has been investigated by means of optical emission spectroscopy (OES) with actinometric analysis for some relevant species such as CN and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Other DMASs without SiH bonds such as dimethylamino‐trimethylsilane (DMATMS, Me 3 SiNMe 2 ) and tris(dimethylamino)methylsilane (TDMAMS, MeSi(NMe 2 ) 3 ) have been tested under the same experimental conditions. Coatings with similar characteristics have been obtained with all the DMASs as well as indications of a different involvement of the NMe 2 and SiMe groups in the film formation 20. DMASs without SiH functionalities have been chosen since they are safer and less corrosive.…”
Section: Introductionmentioning
confidence: 84%
“…Other DMASs without SiH bonds such as dimethylamino‐trimethylsilane (DMATMS, Me 3 SiNMe 2 ) and tris(dimethylamino)methylsilane (TDMAMS, MeSi(NMe 2 ) 3 ) have been tested under the same experimental conditions. Coatings with similar characteristics have been obtained with all the DMASs as well as indications of a different involvement of the NMe 2 and SiMe groups in the film formation 20. DMASs without SiH functionalities have been chosen since they are safer and less corrosive.…”
Section: Introductionmentioning
confidence: 84%
“…PECVD deposition of APTES is expected to result in reproducible silanized surfaces containing reactive amine groups, with good adhesion to cycloolefin polymer through a siloxane network. The characteristics of PECVD coatings are highly dependent on the nature of the substrate, the precursor and the plasma characteristics including input power and deposition time (Di Mundo 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it was shown that the use of NH 3 / TMS mixture can increase significantly the nitrogen content [18] and an incorporation of 28 at.% of nitrogen was observed. Moreover, other recent studies [19,20] have shown that the use of dimethylaminosilane monomers tested as SiN x precursors such as dimethylaminotrimethylsilane (DMATMS), bis (dimethylamino)dimethylsilane (BDMADMS) and tris(dimethylamino)methylsilane (TDMAMS) allows to obtain nitrogen contents of 10 to 30 at.%, depending on the experimental parameters.…”
Section: Chemical Compositionmentioning
confidence: 99%